Alternative treatment of recurrent Clostridioides difficile infection in adults by fecal transplantation: an overview of phase I–IV studies from Clinicaltrials.gov - Obaid, Najla A. (Frontiers in Microbiology, 2024)
Background Fecal microbiota transplantation (FMT) is an interventional approach to treat chronic and recurrent Clostridioides difficile infection (CDI). However, there is insufficient evidence regarding its effectiveness and safety. Clinical trials have been conducted to inspect the safety and effectiveness of FMT with and without comparison to pharmacological treatments. Aim This review explored the treatment of CDI in adults using FMT and evaluated the safety of this intervention based on phase I–IV studies registered on Clinicaltrials.gov. Method A comprehensive search of Clinicaltrials.gov was conducted to identify relevant studies that investigated CDI in adults. Data on study type, study design, sample size, intervention details, and outcomes related to FMT were examined and evaluated. Results In total, 13 clinical trials on FMT for CDI published through 17 November 2023 were identified, all of which were interventional studies. The investigation focused on both terminated and completed studies. Basic and advanced outcome measures were examined. Conclusion Some studies were terminated during phase II, and FMT was less effective than antibiotics such as vancomycin and fidaxomicin. However, colonoscopy and oral FMT were explored in several completed studies with promising results, but the evidence remains limited and inconclusive.